2017
DOI: 10.1038/s41598-017-10098-3
|View full text |Cite
|
Sign up to set email alerts
|

Meta-signature of human endometrial receptivity: a meta-analysis and validation study of transcriptomic biomarkers

Abstract: Previous transcriptome studies of the human endometrium have revealed hundreds of simultaneously up- and down-regulated genes that are involved in endometrial receptivity. However, the overlap between the studies is relatively small, and we are still searching for potential diagnostic biomarkers. Here we perform a meta-analysis of endometrial-receptivity associated genes on 164 endometrial samples (76 from ‘pre-receptive’ and 88 from mid-secretory, ‘receptive’ phase endometria) using a robust rank aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
180
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(199 citation statements)
references
References 117 publications
7
180
1
2
Order By: Relevance
“…No endometrium peristalsis wave within 3 min; score, 1; c two-dimensional gray-scale mode; endometrial thickness, 6.0 mm; score, 1; endometrial type, type C; score, 1; d 2D color Doppler mode; a little blood flow in the subendometrium; score, 2; e threedimensional mode; EV, 1.56 cm 3 ; score, 1; f three-dimensional mode; VFI, 0.027; score, 2 assessment of endometrial repair, but these features have limitations in the monitoring of disease condition and the diagnosis and treatment of diseases. In recent years, increasing attention has been paid to the role of recovery of endometrial receptivity in the endometrial repair [4,[14][15][16]. Although many studies have been conducted to investigate the endometrial receptivity, the methods in these studies are often different and there are no widely accepted criteria for the assessment of endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…No endometrium peristalsis wave within 3 min; score, 1; c two-dimensional gray-scale mode; endometrial thickness, 6.0 mm; score, 1; endometrial type, type C; score, 1; d 2D color Doppler mode; a little blood flow in the subendometrium; score, 2; e threedimensional mode; EV, 1.56 cm 3 ; score, 1; f three-dimensional mode; VFI, 0.027; score, 2 assessment of endometrial repair, but these features have limitations in the monitoring of disease condition and the diagnosis and treatment of diseases. In recent years, increasing attention has been paid to the role of recovery of endometrial receptivity in the endometrial repair [4,[14][15][16]. Although many studies have been conducted to investigate the endometrial receptivity, the methods in these studies are often different and there are no widely accepted criteria for the assessment of endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…We identified ITGB4 as a unique marker of trophoblast cells. LAMB3 , which plays an important role in the endometrial extracellular matrix during early pregnancy [33], may be signaling trophoblasts through ITGB4 and mediating invasion into maternal tissue during placentation, and needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Of the hundreds of gene expression changes typically identified by microarray, relatively few are common to more than two studies (Haouzi, Dechaud, Assou, De Vos, & Hamamah, ; Horcajadas et al, ). Although the metasignature of endometrial receptivity has recently been described (Altmae et al, ), comparisons of proteomic data with published gene expression data in similar cohorts of women (Burney et al, ; Chen et al, ; Haouzi et al, ) have also revealed an overall lack of correlation between the two, suggesting that posttranscriptional or translational regulation is an important feature of endometrial remodeling.…”
Section: Discussionmentioning
confidence: 99%